Transformations of the Bachelor's Degree in Computer Education to reduce the effects of Covid. (Encuentros, 2020)
The article addresses the training of graduates in computer education from the current post-pandemic conditions. At first, an analysis is made of current solutions regarding the training of university professionals and the impossibility of assuming them from the social and historical context. In a second moment, the current conditions of Cuban higher education in general and in particular of the degree are described. Later the methods used are described and finally the results obtained.Keywords: teacher training, computer science education, computer science teacher training, pandemic training.